Human factor impact in military aircraft maintenance - Marinković, Srboljub J.; Drenovac, Aleksandar Ž. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Aircraft maintenance, as a specific field of military materiel maintenance, is characterized by high reliability standards, based on regulations and technical standards. A system approach to maintenance represents the key element of maintenance quality, while aircraft maintenance staff has a crucial influence on the final outcome of aircraft maintenance. Introduction Aircraft maintenance represents the most significant aspect of preventive measures of flight safety, as well as a type of engineering in safety design. Being a specific kind of maintenance, with particular importance, constraints, demands and characteristics, aircraft maintenance is carried out through a multi-level technical organization. There are numerous manifestations of the human factor influence, characterized by both subjective and objective parameters, affecting aircraft maintenance. The importance of the human factor The human factor becomes more and more important, gaining even a key role in aircraft maintenance due primarily to the importance of the human factor in flight safety through the establishment and implementation of a documented system of aircraft maintenance, based on the guidelines for each type of aircraft and all items of equipment, assemblies and aggregates. Constant improvement of aviation technology has led to the 20:80 mechanical failure to the human factor ratio in aircraft accidents, with a constant decrease in the absolute number of errors due to the development of analytical, organizational, managerial, and technical methods, techniques and tools. The influence of the human factor Statistics shows that 12-15% of all aviation accidents occurred due to aircraft maintenance failures, caused by various psychological, social, and physical factors influencing the personnel in aircraft maintenance. World aviation practice has recognized twelve elements of the negative impact of the human factor in aircraft maintenance, so that managers at all levels should pay considerable attention to each of them in order to achieve a preventive, maximum positive impact. Human resource management in aircraft maintenance The essential maintenance staff are engineers and technicians with not only high technical knowledge, but also with specific approaches and ways of thinking as well as analytical, detail-oriented and problem-solving skills, perseverance and patience in finding and resolving errors included. Given that such personnel is scarce and represent a significant public resource, it is necessary to pay special attention to their treatment, predictable career guidance and constant development. On the job learning In all world organizations, no matter which activity primarily involved in, great importance is attached to an institution of learning known as "on-the-job-learning" and "on-the-job-training." This is particularly important in maintenance units, where the induction is done through a number of stages, with different levels and forms of education and training. This approach is particularly important because of specific resources and literature, as well as trained staff, since efficient and effective learning can be carried out only in the work environment in which all resources are available. Motivational aspects of the human factor in aircraft maintenance Maintenance work on the aircraft is one of the most challenging tasks from the psychological, social, vocational and physical aspect. A large number of activities in a variety of aircraft maintenance procedures is implemented through teamwork, where it is necessary to achieve the highest possible degree of cooperation, with common interests and higher motives. The implementation of the common task depends on the motivational aspect of each individual, so leaders of all levels must take into account meeting the needs of individuals in accordance with the pyramidal hierarchy of needs, in order to have maximally motivated and dedicated maintenance staff. Human factor risk management Risk management in aircraft maintenance must be carried out through a process approach, where the elements of the process are: identification, qualitative and quantitative analysis, development of a strategy and a plan of the responses to risks, strategy and plan implementation, as well as the assessment of residual risk. Constant monitoring and control are necessary as well as taking measures for continuous process improvement. A continuous improvement of risk management processes is thus provided. In all activities, it is necessary to implement the maximum risk reduction and insist on respecting rules, procedures and preventive actions. Modern approach- - non punitive error reporting International aviation regulations require the positive practice of non punitive reporting which provides a systematic collection of data on human errors in aircraft maintenance ,in order to take action to improve the situation. The sole purpose of this reporting is the prevention of accidents and incidents and not to attribute the determination of guilt or other responsibilities. Accepting the truth of the possibility of a human error should result in the adoption of new attitudes at all levels of management, and in a new approach encouraging the principles of truth. Conclusion With the advancement of aviation technology, the human factor will increasingly be at the forefront. Therefore, it is necessary to establish a new approach to human factors in aircraft maintenance, and abandon the old dogma of the infallibility of strict maintenance, as well as the sole responsibility of individual end-executors for maintenance errors, since the impact of management and applied organizational methods is demonstrated as well as that of psycho-social factors. Aircraft personnel engaged in the maintenance of such an important resource should be given special attention, especially in terms of providing optimal working conditions, career guidance, enabling the development and establishment of cooperation and exchange of experiences with other institutions. To improve the situation, it is necessary to adopt the concepts of international standards, and apply the principle of non-punitive reporting and acceptance of a human error in order to more effectively address the factors of error occurrence and aircraft safety. Consideration of the factors and the impact of the human factor has become an integral part of the content of the training, but also an area that needs to be given special attention through regular seminars for all participants in the planning process, including the most senior leaders in the Air Force of the Serbian Armed Forces.